Pola Asuh Otoriter, Kontrol Diri Dan Perilaku Seks Bebas Remaja SMK - Yuniar Angelina, Dika (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract. This study aims to find the relationship between authoritarian parenting, self-control and sexual behavior in adolescents SMK free. The subjects were 109 students of class XI majoring in Computer Engineering and Networks SMKN 1 Slahung Ponorogo. Data collection tool used is scale free sex, authoritarian parenting scale and the scale of self-control. The third scale models a likert scale consisting of five alternative answers. While the data analysis method used is regression analysis. The analysis showed that the variables jointly authoritarian parenting and self-control did not correlate with variable free sex teen. Effective contribution of variable authoritarian parenting and self-control together to give effect by 03,2% against the free sex teen. 97,0% so there are other variables that influence the behavior of free sex teen than two variables X are investigated.Keywords : authoritarian parenting, self-control and free sex teen